Bioactive Compounds with Pesticide Activities Derived from Aged Cultures of Green Microalgae - Alethia A. Brito-Bello; Damar Lopez-Arredondo (Biology, 2023)
The excessive use of synthetic pesticides has caused environmental problems and human health risks and increased the development of resistance in several organisms. Allelochemicals, secondary metabolites produced as part of the defense mechanisms in plants and microorganisms, are an attractive alternative to replace synthetic pesticides to remediate these problems. Microalgae are natural producers of a wide range of allelochemicals. Thus, they provide new opportunities to identify secondary metabolites with pesticide activities and an alternative approach to discover new modes of action and circumvent resistance. We screened 10 green microalgae strains belonging to the Chlorophyta phylum for their potential to inhibit the growth of photosynthetic and nonphotosynthetic organisms. Bioassays were established to assess microalgae extracts’ effectiveness in controlling the growth of Chlorella sorokiniana, Arabidopsis thaliana, Amaranthus palmeri, and the model nematode Caenorhabditis elegans. All tested strains exhibited herbicidal, nematocidal, or algicidal activities. Importantly, methanol extracts of a Chlamydomonas strain effectively controlled the germination and growth of a glyphosate-resistant A. palmeri biotype. Likewise, some microalgae extracts effectively killed C. elegans L1 larvae. Comprehensive metabolic profiling using LC-MS of extracts with pesticide activities showed that the metabolite composition of Chlamydomonas, Chlorella, and Chloroidium extracts is diverse. Molecules such as fatty acids, isoquinoline alkaloids, aldehydes, and cinnamic acids were more abundant, suggesting their participation in the pesticide activities.